2023
DOI: 10.1111/jipb.13439
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol induces flower bud formation via the MADS‐box transcription factor EjCAL in loquat

Abstract: Sorbitol is an important signaling molecule in fruit trees. Here, we observed that sorbitol increased during flower bud differentiation (FBD) in loquat (Eriobotrya japonica Lindl.). Transcriptomic analysis suggested that bud formation was associated with the expression of the MADS-box transcription factor (TF) family gene, EjCAL. RNA fluorescence in situ hybridization showed that EjCAL was enriched in flower primordia but hardly detected in the shoot apical meristem. Heterologous expression of EjCAL in Nicotia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…The accumulation of carbohydrates in fruits is synergistically regulated by various TFs ( Ren et al., 2023 ). However, due to the delayed publication of the loquat genome and the absence of a stable gene function verification system, there have been few reports on TFs associated with the sugar metabolism pathway in loquat ( Xu et al., 2023 ). In this study, the comparison of protein sequences and promoter region of S6PDH ( EVM0006243 , EVM0044405 ) between TBY and TBW showed that there was no structural variation affecting gene function or expression, indicating that TFs may be responsible for the rapid up-regulation of S6PDH before maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of carbohydrates in fruits is synergistically regulated by various TFs ( Ren et al., 2023 ). However, due to the delayed publication of the loquat genome and the absence of a stable gene function verification system, there have been few reports on TFs associated with the sugar metabolism pathway in loquat ( Xu et al., 2023 ). In this study, the comparison of protein sequences and promoter region of S6PDH ( EVM0006243 , EVM0044405 ) between TBY and TBW showed that there was no structural variation affecting gene function or expression, indicating that TFs may be responsible for the rapid up-regulation of S6PDH before maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The positive influence of exogenous hyperoside on flower buds indicates its great prospects in horticulture and agriculture applications. A recent study reported that sorbitol could promote the accumulation of hyperoside and ultimately prompt loquat flower bud differentiation through ERF12-CAL-GAT signaling pathway, again demonstrating the significant role of hyperoside in flower bud formation by potentially influencing downstream genes [ 41 ]. Therefore, it is of great significance to synthesize hyperoside in an efficient way.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, MADS-box genes are considered to operate as regulators of flower morphogenesis or pollen maturation ( Michaels and Amasino, 1999 ; Yu et al., 2014 ). For example, the loquat MADS-box genes EjCAL can promote the flower bud differentiation process ( Xu et al., 2022 ). The connection between MADS-box genes and fruit lignification could not be established until the loquat EjAGL65 was first identified ( Ge et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%